Treatment Of Salt Attack And Rising Damp In Heritage Buildings In Penang, Malaysia - Ahmad, A Ghafar; Rahman, Haris Fadzilah Abdul (Penerbit Universiti Sains Malaysia, 2010)
Of the common building defects that occur in heritage buildings in Penang, Malaysia, salt attack and rising damp are considered the most challenging, particularly for building conservation. Both problems of salt attack and rising damp are closely associated. Moisture from the rising damp makes the building‟s existing salts soluble, or ground water that contains salt finds its way through the building wall. This moisture then evaporates on or just below the wall‟s surface, leaving salt residue behind. High salt concentrations in masonry walls cause extensive fretting and crumbling of the lower parts of walls. These are formations gradually contribute to building dilapidation and reduce the building‟s aesthetic value. Sodium chloride and calcium sulphate are commonly found in masonry walls, apart from other forms of salts. The sources of these salts may be natural or manmade. This paper is based on research into the problems of salt attack and rising damp in heritage masonry buildings in Penang, Malaysia. Based on a case study of five buildings in Penang, the research findings showed that these buildings faced several common building defects, including salt attack and rising damp. Treatment guidelines for salt attack and rising damp are proposed within the Malaysian context of architectural heritage and climatic conditions.